2017
DOI: 10.1039/c7cp04337f
|View full text |Cite
|
Sign up to set email alerts
|

Computational design of pH-switchable control agents for nitroxide mediated polymerization

Abstract: In the present work we use accurate quantum chemistry to evaluate several known and novel nitroxides bearing acid-base groups as pH-switchable control agents for room temperature NMP. Based on G3(MP2,CC)(+)//M06-2X/6-31+G(d) calculations with UAKS-CPCM/M06-2X/6-31+G(d) solvation corrections, a number of novel nitroxides are predicted to be suitable for controlled polymerization of bulk styrene at room temperature when deprotonated (i.e. negatively charged), while remaining inert when neutral. These include an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…In implementing the work experimentally in solution, the challenge is to balance the need for a low polarity solvent (so as to maximise field) with the limited solubility of charged species under such conditions. Nonetheless we have shown experimentally that such compromises are possible and that sizeable pH switches are achievable under practical conditions 11,13 Given this success, the question arises whether or not this approach can be used more broadly. In particular, could charged groups provide a low-tech way to mimic electrostatic catalysis of Diels-Alder reactions?…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In implementing the work experimentally in solution, the challenge is to balance the need for a low polarity solvent (so as to maximise field) with the limited solubility of charged species under such conditions. Nonetheless we have shown experimentally that such compromises are possible and that sizeable pH switches are achievable under practical conditions 11,13 Given this success, the question arises whether or not this approach can be used more broadly. In particular, could charged groups provide a low-tech way to mimic electrostatic catalysis of Diels-Alder reactions?…”
Section: Introductionmentioning
confidence: 97%
“…However, we have recently provided computational and experimental proof of concept that electrostatic effects can be provided by charged functional groups in nitroxide chemistry (Figure 1d). [9][10][11][12][13] By using a charged functional group, a local electric field is generated, with its orientation relative to the reaction centre determined by its location. An additional benefit of this approach is that these functional groups are pH switchable; that is, the charge and hence field can be turned on or off at will with simple pH changes.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] To address these problems, various groups have examined using alternative stimuli to trigger alkoxyamine fragmentation, including light [7][8][9] and chemical additives, [10][11] with mixed success. Recently, we demonstrated that both charged-functional groups [12][13][14] and electric fields 15 can be used to induce alkoxyamine homolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that this can be achieved at the nanoscale using scanning tunneling microscopy, 4,5 and, at larger scales, using electrodes 6 charged insulators, 7 charged functional groups, [8][9][10] and metal ions. [11][12][13] While catalysis has been the main focus until now, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] perhaps the most interesting applications stem from the ability of electric fields to change outcome of a reaction. For instance, theoretical studies have shown that the regio-and stereoselectivity of a Diels-Alder reaction can be changed with either external oriented fields 16,17 or appropriately placed charged functional groups.…”
Section: Introductionmentioning
confidence: 99%